2017
DOI: 10.4317/jced.53522
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different intra canal medicaments on the push out bond strength of endodontic sealers

Abstract: BackgroundOne of the essential properties of the root canal sealers is the adhesion to root canal dentin and their higher bond strength decreases the microleakage. The aim of the present study was to compare the effect of Different Intracanal medicaments on the push out bond strength of AH26 and MTA Fillapex sealers.Material and MethodsA total of 104 one-rooted extracted human teeth were divided into 4 (n=26) experimental groups. After the cleaning and shaping, the root canals were filled with Ca(OH)2, trianti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
0
8
1
Order By: Relevance
“…25 26 CH alone or in combination with CHX, TAP, and DAP is commonly used as intracanal medicaments. 27 However, their use is associated with some concerns regarding their effects on root dentin. 21 This is especially important for final restoration of tooth crown since endodontically treated teeth have often lost a large amount of tooth structure, and coronal restoration of these teeth requires retention, which is often provided by intracanal posts.…”
Section: Discussionmentioning
confidence: 99%
“…25 26 CH alone or in combination with CHX, TAP, and DAP is commonly used as intracanal medicaments. 27 However, their use is associated with some concerns regarding their effects on root dentin. 21 This is especially important for final restoration of tooth crown since endodontically treated teeth have often lost a large amount of tooth structure, and coronal restoration of these teeth requires retention, which is often provided by intracanal posts.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that calcium hydroxide with 2% chlorhexidine gel did not influence the bond strength values for either material analyzed for coronal sealing, indicating that it is possible to use it safely with regard to its possible impact on coronal sealing in teeth undergoing revitalization procedures. Some studies have analyzed the effects of 2% chlorhexidine gel on bond strength, concluding that this substance yielded higher values than calcium hydroxide and Metapex when MTA Fillapex was used as a filling material [29], although it did not change the bond strength of fiberglass posts cemented with resin cement [30].…”
Section: Discussionmentioning
confidence: 99%
“…Metapex is a new root canal filling material containing calcium hydroxide, iodoform, and silicone oil media. The efficacy of Metapex against bacterial activity in the root canal is superior in comparison to plain calcium hydroxide [ 7 ]. In the present study, Metapex was chosen as a test material given its chemical composition compared to plain calcium hydroxide on the bond strength of sealers and the dentin [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of Metapex against bacterial activity in the root canal is superior in comparison to plain calcium hydroxide [ 7 ]. In the present study, Metapex was chosen as a test material given its chemical composition compared to plain calcium hydroxide on the bond strength of sealers and the dentin [ 7 ]. A combination of anti-bacterial triple antibiotic paste (TAP) was introduced to treat, regenerate, and revascularize necrotic pulp with an open apex.…”
Section: Introductionmentioning
confidence: 99%